Non-Performing Finance in Sharia Financial Institutions in Indonesia: A Case Study Of BPRS Adeco (Aceh Development Corporate) - Nur Hidayah; Tabrani Tabrani (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
High level of Non-Performing Finance (NPF) has become one of risks facing intermediary financial institutions including Islamic banks. Indonesia’s Financial Authority found that NPF ratio of Islamic banks is relatively higher (4,12%) that the one of conventional banks (2,96%) (OJK 2017). Literature indicate the influence of bank’s internal and external factors on high NPF. This study aims to analyze the factors that influence the high level of NPF and its settlement and strategies to reduce the level of NPF in Sharia Rural Banking (BPRS/Bank Perkreditan Rakyat Syariah). Taking BPRS Adeco (Aceh Development Corporate) in Langsa City District, Aceh, as a case study, this research takes a qualitative approach. Through a survey to 26 BPRS Adeco employees and semi-structured interviews with 4 employees, this study found three factors leading to an increase in the NPF ratio, namely weak bank’s financing risk management, changing economic conditions and regulations, and the conditions of customers who are vulnerable to socio-economic change. It found that the NPF can be gradually resolved by intensifying the communication to the delinquent customers followed by policies of restructuring the customers’ financing. It also found that the strategies to reduce NPF ratios include improving bank risk financing management, upgrading the quality of human resources in risk management, and providing business mentoring and coaching to the customers. It can be concluded that the strategies made by the BPRS ADECO succeeded in reducing the NPF rate from 15.62% in the June 2012 period to 3.60% in the December 2018 period. The finding implies that Islamic financial institutions, including BPRS, urgently need good finance risk management, particularly in monitoring the financed customers’ business and in mitigating external conditions of the economy and their changing related regulations in order to settle the problem of non-performing finance and to strengthen their finance risk management.